Validasi Metode Ultra High Peformance Chromatography Double Mass Spectrophotometry (UHPLC-MS/MS) untuk Analisis Kurkumin pada Ekstrak Etanol Kunyit (Curcuma longa) dengan Berbagai Perbandingan Konsentrasi - Ihsan, Bachtiar Rifai Pratita; Maysaroh, Intan; Nurhayati, Ika Putri (Brawijaya University, 2018)
Curcumin is a chemical agent which known to have many benefits in medical healthcare. Turmeric is a plant which contains curcumin. Curcumin can be obtained by maceration. The research of comparing ethanol concentration for maceration turmeric is limited. This research is using 3 different ethanol concentration i.e. ethanol 96%; ethanol 80% and ethanol 70%. The extract which obtained from maceration is analyzed with UHPLC-MS/MS instrument which had validated before. The parameter of method validation which analyzed in this research are selectivity, linierity, accuration, presicion and LOD LOQ. The result of curcumin content measurement in sample ethanol extract 96%; 80%; and 70% are 17,64 ± 2,100 %; 16,99 ±2,494 % and 7,73 ± 4,950% respectively.Keywords: Curcumin, turmeric, Curcuma longa, maceration, ethanol, UHPLC-MS/MS, method validation